Multimodality imaging of a subtotally obstructive right ventricular myxoma in an asymptomatic 10-year-old girl - Gesa Wiegand; Ludger Sieverding; Ulrich Kramer; Susanne Haen; Michael Hofbeck (Wolters Kluwer Medknow Publications, 2014)
A 10-year-old girl presented with a supraventricular tachycardia. A heart murmur was detected during a clinical examination; therefore, echocardiography was performed. This revealed a giant right ventricular myxoma that subtotally obstructed the right ventricular outflow tract. A myxoma in the right ventricle is uncommon in children. This rare intracardiac tumor was examined using multimodality imaging, and the patient underwent surgical resection. The pathologic features confirmed our suspicion and revealed an encapsulated tumor with myxomatoid stroma containing focal hemorrhages.